2015
DOI: 10.5582/ddt.2015.01025
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides: Candidates of promising vaccine adjuvants

Abstract: Aluminium-based adjuvants remain the only adjuvants approved for human use in the USA for over 80 years because of alum's simplicity, tolerability, safety and cost-efficiency. Recent development of vaccines, especially the increasing applications of recombinant subunit and synthetic vaccines, makes aluminium adjuvants cannot stimulate enough immunity to the antigens, since aluminium adjuvants can only induce Th2 type immune responses. So, novel adjuvants are urgent to make up the disadvantages of aluminium adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…21e25 Advax coadministered with vaccines induces Th1 (IgG2a, IL-2, IFN-g) and Th2 (IgG1, IgA, IL-5, IL-6) responses. 26 More details on inulin are given elsewhere in this book.…”
Section: Plant Polysaccharidesmentioning
confidence: 99%
“…21e25 Advax coadministered with vaccines induces Th1 (IgG2a, IL-2, IFN-g) and Th2 (IgG1, IgA, IL-5, IL-6) responses. 26 More details on inulin are given elsewhere in this book.…”
Section: Plant Polysaccharidesmentioning
confidence: 99%
“…With advances in vaccine technology, natural polysaccharide adjuvants have emerged and have been used as immunopotentiators that improve antibody levels and promote cellular immunity . Research has demonstrated that adjuvant PCP‐II elicited antigen‐specific antibody levels in mice immunized with influenza vaccine and hepatitis B surface antigen (HBsAg).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reports of Coley's toxins (which were a mixed bacterial vaccine), a wide array of different immune activators have been tested for their ability to stimulate the immune system to combat cancer. The best known anticancer immune activators are probably BCG (used clinically for bladder cancer) and CpG oligodeoxynucleotide, but polysaccharides have also been tested . N ‐dihydrogalactochitosan (GC) is a new immune activator that was originally prepared by attaching galactose molecules to the amino groups of chitosan, a glucosamine polymer, in order to improve solubility in water at neutral pH, and to overcome problems of sterile filterability in the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%